The Effect of Hexagon Fraud in Detecting Fraud Financial Statements (Empirical Study on Financial Sector Companies Listed on the Indonesia Stock Exchange 2017-2021) - Julia, Julia; Yunita, Anggraeni (Future Science / FSH-PH Publications, 2022)
This study aims to determine the effect of hexagon fraud (stimulus, opportunity, rationalization, capability, ego, and collusion) in detecting financial statement fraud. The dependent variable used in this study is financial statement fraud as proxied by earning management, while the independent variables are financial target, financial stability, change in directors, ineffective monitoring, change in auditors, frequent number of CEO's picture, and political connection. This study uses secondary data in the form of financial reports and annual reports. The population in this study is the financial sector companies listed on the Indonesia Stock Exchange in 2017-2021 as many as 89 companies. The sampling technique used purposive sampling method with a sample of 19 companies. The data analysis technique uses panel data regression analysis which is processed using the Eviews 12 program. The results of this study indicate that simultaneously financial targets, financial stability, change in directors, ineffective monitoring, change in auditors, frequent number of CEO's picture, and political connection have an effect on detecting financial statement fraud. Furthermore, partially financial targets and financial stability have a positive effect in detecting financial statement fraud. Meanwhile, change in director, ineffective monitoring, change in auditor, frequent number of CEO's picture, and political connection have no effect in detecting financial statement fraud.